2015
DOI: 10.1128/jcm.02046-15
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Variable Enterococcal Bacteremia

Abstract: e Vancomycin-variable enterococcus (VVE) is an emerging pathogen. VVE isolates initially appear phenotypically susceptible to vancomycin but possesses the vanA gene and can develop in vitro and in vivo resistance to vancomycin. We report a case of VVE bacteremia and describe how VVE poses diagnostic and therapeutic dilemmas. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Transmission of the vanA gene cassette is largely due to horizontal gene transfer of plasmids containing Tn 1546 -like elements [ 9 ]. Because this also seems to be the case for VVE, and because the frequent genetic rearrangements mean that VVE can be either resistant or susceptible to vancomycin, we believe that control of VVE in our geographic area will be important if we wish to protect our hospitals and patients from VRE [ 7 ]. Institutions or regions wishing to prevent the development of endemic VRE within their hospitals should be alert to the risk of VVE strains, and should consider using PCR for vanA/vanB genes for screening to contain their spread as needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of the vanA gene cassette is largely due to horizontal gene transfer of plasmids containing Tn 1546 -like elements [ 9 ]. Because this also seems to be the case for VVE, and because the frequent genetic rearrangements mean that VVE can be either resistant or susceptible to vancomycin, we believe that control of VVE in our geographic area will be important if we wish to protect our hospitals and patients from VRE [ 7 ]. Institutions or regions wishing to prevent the development of endemic VRE within their hospitals should be alert to the risk of VVE strains, and should consider using PCR for vanA/vanB genes for screening to contain their spread as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their susceptibility to vancomycin, VVE escape the traditional detection methods for vancomycin-resistant enterococci (VRE), which might be associated with under-diagnosing and silent dissemination of VVE in healthcare facilities. Indeed, VVE have often been reported as clusters causing hospital outbreaks [ 3 5 , 7 ]. Worryingly, both in vivo and in vitro data show that VVE have the ability to revert into vancomycin-resistant phenotypes upon vancomycin exposure [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This bacteraemia case with VVE and MRSA raises several important questions, previously discussed by Downing et al 6 Should vancomycin be avoided in patients with serious VVE infections? A patient colonised with this organism was recently described, and it was shown that the isolate developed resistance to vancomycin in vivo during vancomycin therapy.…”
mentioning
confidence: 87%
“…as well as recognition of relatively frequent detection of MPO mRNA in ALL blasts, which does not correlate consistently with immunophenotyping and cytochemical findings. 1,6 Advances in molecular techniques have resulted in better subclassification of acute leukaemias and improved diagnostic certainty. 2,6 Several sequencing studies have demonstrated a large degree of genomic heterogeneity in MPAL as well as differences between MPAL subtypes (B/myeloid and T/myeloid), although notably only a small number of triphenotypic leukaemia were included in these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation